2021
DOI: 10.3390/s21092898
|View full text |Cite
|
Sign up to set email alerts
|

Studying Collaboration Dynamics in Physical Learning Spaces: Considering the Temporal Perspective through Epistemic Network Analysis

Abstract: The role of the learning space is especially relevant in the application of active pedagogies, for example those involving collaborative activities. However, there is limited evidence informing learning design on the potential effects of collaborative learning spaces. In particular, there is a lack of studies generating evidence derived from temporal analyses of the influence of learning spaces on the collaborative learning process. The temporal analysis perspective has been shown to be essential in the analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…These angles include public engagement, gender, sustainability, science education or inclusion. The TIDE research group at UPF is committed to gender and international diversity, as reflected in its composition (currently over 20 members with equal gender balance and 13 different nationalities), and has started to incorporate the gender, science education and inclusion perspectives determinedly in their studies (e.g., Vujovic et al, 2021;Martínez, Santos & Hernández-Leo, 2021). Mutual inspiration through shared good practices in all angles of responsibility in data and science cultures in educational research will definitely contribute to better science with increasingly positive social impact.…”
Section: Discussionmentioning
confidence: 99%
“…These angles include public engagement, gender, sustainability, science education or inclusion. The TIDE research group at UPF is committed to gender and international diversity, as reflected in its composition (currently over 20 members with equal gender balance and 13 different nationalities), and has started to incorporate the gender, science education and inclusion perspectives determinedly in their studies (e.g., Vujovic et al, 2021;Martínez, Santos & Hernández-Leo, 2021). Mutual inspiration through shared good practices in all angles of responsibility in data and science cultures in educational research will definitely contribute to better science with increasingly positive social impact.…”
Section: Discussionmentioning
confidence: 99%
“…They found differences between the gaze patterns of students who solved the graph tasks correctly and incorrectly; for example, incorrect solvers shifted their gaze from the graph to the x -axis and from the question to the graph comparatively more often than correct solvers. The last article of this group by Vujovic et al [ 29 ] used collected audiovisual data, within a collaborative activity in a co-located physical learning space, to explore the effects of table shape on collaboration when different group sizes and genders are considered. They found that table shape influences student behavior when considering different group sizes and genders.…”
Section: Overview Of the Special Issuementioning
confidence: 99%
“…Exploring the dynamics within digital discourse digital text (Gašević et al, 2019;Peeters et al, 2020;Shaffer, 2017). ENA has been found to provide additional insights into the dynamics of CMC, as well as into associated learning and teaching processes (Vandenberg, 2021;Vujovic et al, 2021).…”
Section: Computer-mediated Communication (Cmc) Text Analyticsmentioning
confidence: 99%